If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(v+5)=-4v+8
We move all terms to the left:
-2(v+5)-(-4v+8)=0
We multiply parentheses
-2v-(-4v+8)-10=0
We get rid of parentheses
-2v+4v-8-10=0
We add all the numbers together, and all the variables
2v-18=0
We move all terms containing v to the left, all other terms to the right
2v=18
v=18/2
v=9
| -8=-5w+3(w-6) | | 5v+45=-9(v+9) | | 29.6t=207.2 | | 0.1-x=0.45x | | 0.1-x=0.315x | | 3x+2=(2x+20)/2 | | 3x+2=2x+20/2 | | 1=9x+4 | | 4-(3x-3)=12x+2 | | 9y+1=0 | | -23+z=-44 | | 0.1=0.315x+x | | 12(x-1)^2-28(x-1)=24 | | 30z-7=-8z | | 2x^2+3(0)=6 | | 4^2x=7^x-1 | | 4^(2x=7^(x-1) | | (1+i)10=1.375 | | 2(1-9x)=4(7-5x) | | 10z-3=-7z | | 1-(6/x)-(27/x)=0 | | 20y-11=360 | | z/4 =5/12 | | z/4=5/12 | | 4x/15=75 | | 4+2(z-2)=-3z+4= | | 10+10i=1.375 | | 3(d-7)-10(4d-5)=5 | | x(2x+2)=-8 | | 2x²+72x=-648 | | x(2x+2)=8 | | 13+y=-2 |